Detection of Brugia malayi microfilaria/Larvae in mosquito using Polimerase Chain Reaction. - Dyah Haryuningtyas; Didik Tulus Subekti (Indonesian Center for Animal Research and Development (ICARD), 2008)
Lymphathic filariasis that is also known as elepanthiasis is caused by infestation of 3 species nematode Wuchereria bancrofti, Brugia malayi and Brugia timori. In Indonesia 70% filariasis case caused by Brugia malayi. Mosquito species from genus Anopheles, Aedes, Culex, Mansonia and Armigeres are known as vector of this disease. Microfilaria detection on mosquito is one methode to know infection rate in vector population in endemic area.The objectives of the research were to study the ability of Hha1 repeat applicable to detect microfilaria/larvae in a pool of mosquitoes and to get description of adult mosquito night biting population lived in endemic area of filariasis brugian. Mosquito as positive control used in this research come from laboratory of parasitology of FKUI. Mosquito sample from the field was from Binawara and Kolam Kiri villages, South Kalimantan province. Mosquito were trapped then identified by its species. DNA of mosquitoes was extracted and then run by the PCR using Hha 1 repeat primer. Result of the research indicated that adult mosquitoes night biting from Binawara village consist of Culex, Mansonia, Anopheles genus and from Kolam Kiri village only from Mansonia genus. Hha 1 repeat primer is applicable to detect 1 mosquito infected with microfilaria/larvae in a pool of negative mosquitoes. Mosquito samplesfrom the two villages showing negative PCR. Key Words: Filariasis, Brugia Malayi, Vector, Microfilaria, Filaria Larve, PCR